Superhydrophobic Drag-Reduction Spherical Bearing Fabricated by Laser Ablation and PEI Regulated ZnO Nanowire Growth - Weng, Rui; Zhang, Haifeng; Tuo, Yanjing; Wang, Yang; Liu, Xiaowei (Scientific reports, 2017)
The resistance of the bearing is a significant factor affecting the performance of the ball-disk rotor gyroscope. The micro and nano combined surface with low surface energy material modifications can be hydrophobic. This can reduce the drag when the bearing is lubricated by deionized water. Laser ablation method is utilized to form micron-scaled structures on the surface of the stainless steel rotor ball. And the nanostructures are formed by PEI (Polyetherimide) regulated ZnO nanowires growth. After low surface energy material modification, the water contact angle of processed surface was 163° and the sliding angle was less than 4°. The maximum rotational speed was enhanced by up to 82.77% at 1.5 W driving power. Experiments show that the superhydrophobic drag-reduction spherical bearing has good short-term reliability. At 5 V drive voltage, the bearing can extend the rotational speed of ball-disk rotor gyroscope to 35000 rpm, and maintain the normal operation for longer than 40 minutes. This is quite meaningful for short-term-work or one-time-use rotor gyroscopes.